Current resistance status to temephos in Aedes aegypti from different regions of Argentina - Albrieu Llinás, Guillermo (2010)
In Argentina, more than 25,000 cases of dengue were reported in the summer of 2009, even in provinces wherethe disease was formerly absent. We analysed the susceptibility levels to the larvicide temephos in seven populationsof Aedes aegypti, the primary vector of dengue, collected during summer 2007/2008, using the susceptible Rockefellerstrain as a control. Although no control failures were observed during the experiment, a majority of the lethalconcentration and resistance ratio values indicate an incipient resistance. An integrative program to monitor theresistance of Ae. aegypti to insecticides is needed in the country.